2022
DOI: 10.3389/fpsyt.2022.809543
|View full text |Cite
|
Sign up to set email alerts
|

Regressive Autism Spectrum Disorder: High Levels of Total Secreted Amyloid Precursor Protein and Secreted Amyloid Precursor Protein-α in Plasma

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder characterized by social communication difficulties, repetitive behaviors, and parochial interests. Individuals with regressive ASD (RA), a unique subtype, have poor outcomes. Moreover, there are currently no validated blood-based biomarkers for ASD, hindering early diagnosis and treatment. This study was the first to examine plasma levels of total secreted amyloid precursor protein (sAPPtotal), secreted amyloid precursor protein-α (sAPPα),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…29,30 Derangements in amyloid processing may also be involved in ASD. [31][32][33][34] Interestingly, VPA has been found to inhibit g-secretase cleavage of amyloid precursor protein, reducing brain amyloid load and VPA hypocholesterolemic effects could be a mechanism contributing to its favorable impact on ASD via amyloid reduction. 35 This requires further exploration as most studies of this relationship have focused on cognitive impairment in older population and not on developmental effects on amyloid.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Derangements in amyloid processing may also be involved in ASD. [31][32][33][34] Interestingly, VPA has been found to inhibit g-secretase cleavage of amyloid precursor protein, reducing brain amyloid load and VPA hypocholesterolemic effects could be a mechanism contributing to its favorable impact on ASD via amyloid reduction. 35 This requires further exploration as most studies of this relationship have focused on cognitive impairment in older population and not on developmental effects on amyloid.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, increased Aβ levels have been observed in plasma and post-mortem brain samples of adult FXS individuals and in adult Fmr1 KO mice [18,20,37,76], supporting the development-dependent dysregulation of APP processing in FXS. Of note, high levels of sAPPα have also been reported in the plasma of juvenile idiopathic autistic patients [37][38][39][77][78][79][80][81], in ASD individuals with severe clinical manifestations [78][79][80] and subjects with Angelman syndrome [82], suggesting that sAPPα may play a critical role in the pathogenesis of different neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a clinical manifestation that tends to resolve over time is the presence of seizures [6,102]. Interestingly, seizures have also been reported in individuals with ASD [103,104] and with Angelman syndrome [105,106], which share with FXS the excessive sAPPα production [78][79][80]82].…”
Section: Discussionmentioning
confidence: 99%
“…Li X et al [ 49 ] found higher plasma levels of total secreted amyloid precursor protein (sAPPtotal) and of secreted amyloid precursor protein-α (sAPPα) in children with RO-ASD compared to children with non-regressive ASD and typically developing controls. APP is a glycoprotein secreted by glial cells and neurons that promotes neuronal proliferation and migration, cell adhesion, and synapse formation.…”
Section: Discussionmentioning
confidence: 99%